Promising Clinical Outcome With Long Term Follow-Up After Body Gamma Knife Stereotactic Radiosurgery for Patients With Early Stage Non-small Cell Lung Cancer - Li, Hongqi; Li, Jing; Wang, Xuan; Pang, Haifeng; Di, Yupeng; Ren, Gang; Li, Ping; Liu, Chen; Chen, Xiao; Kang, Xiaoli; Wang, Yingjie; Xia, Tingyi (Frontiers in Oncology, 2018)
Introduction: Stereotactic ablative radiosurgery (SRS) or stereotactic ablative body radiotherapy (SABR) is the standard treatment for patients with inoperable early stage non-small cell lung cancer (NSCLC), the body gamma knife SRS (ɤ-SRS) is a special SABR technology developed in China. This study prospectively assessed the clinical outcome, toxicity and cost following body ɤ-SRS for early stage NSCLC. Methods: From 2007 to 2010, a total of 29 patients with early stage NSCLC were prospectively enrolled in this study. The prescription dose for Planning Target Volume (PTV), Clinical Target Volume (CTV), and Gross Target Volume (GTV) were 50, 60, and 70 gray (Gy) in 10 fractions. Isodose curves of 50, 60, and 70% covered at least 100% of PTV, 90% of CTV, and 80% of GTV, respectively. The body ɤ-SRS was delivered 5 days per week and completed in 2 weeks. Results: Median follow-up time was 62.0 (range 11.1-140.3) months. 1-, 3-, 5-year OS rates were 93.1%, 72.0%, 60.3%; PFS rates were 86.2, 64.2 and 48.8%; and LR, RR, and DM rates were 10.9%, 21.4%, 29.0%. The median cost of the body ɤ-SRS during treatment was 4,838 (range 4,615–4,923) dollars and the median cost through 5 years was 36,960 (range 9920-56,824) dollars. Conclusion: With existing clinical data, the body ɤ-SRS is an effective treatment option for patients with medically inoperable early stage NSCLC or patients who do not prefer operation, as they may benefit from the minimized toxicity. Due to excellent cost effectiveness, the availability of the body ɤ-SRS will expand, especially in developing nations, and underdeveloped countries.